ANALYSIS OF DETERMINANTS OF INFORMAL SECTOR GROWTH IN NIGERIA, 1991-2021 - Opara, Godstime Ikechukwu; Chikezie, Adanna (African Journal of Social and Behavioural Sciences, 2022)
This study investigated the determinants of informal sector growth in Nigeria from 1991 to 2021. The determinants of informal sector growth identified in the study were percentage of informal sector players that have accessed credits, skill development programmes organized for the informal sector and percentage of total labour force in the informal sector. The study utilized informal sector density (estimated percentage of informal businesses in Nigeria) as a measure of informal sector growth in Nigeria. The data used were secondary data obtained from the collaborative survey of the World Bank with the Federal Office of Statistics (FOS) and Nigerian Institute for Social & Economic Research (NISER). The informal sector referred to in the World Bank collaborative survey were 1800 each from the six geo-political zones of the country making it a total of 10,800 informal businesses. Data were analyzed using the Error Correction Model technique within the framework of the Multiple Least Squares methodology. Findings revealed that the percentage of informal sector players that have accessed credits and the skill development programmes organized for the informal sector have negative relationships with informal sector density in Nigeria. Also, the percentage of total labour force in the informal sector had positive and increasing effect on informal sector density in Nigeria. The study concluded that the decreasing effect of the skills and credits acquired by the informal sector players on informal sector density was as expected because these would further enhance the formalization of the activities of the informal sector. It was recommended that government should further enhance access of the informal sector not only to financial credits but also skill sets which should be a continuous process.